Future of Work in Asia: Transforming Work Models, Workforce Dynamics and Workplace Technology - Chorng Yuan, Fung (Springer Nature Switzerland AG, 2025)
One of a series of titles on the Futures of Asia, this book explores diverse facets of Asia’s work landscape during the transformative 2020s, offering insights into pivotal transformations and potential trajectories. The covered topics include future work models, the role of technology in the future workplace, the dynamics of the future workforce, and the evolving landscape of work. Examining the topics from corporate foresight and past-future to technological trends and environmental shifts, this book showcases a collaborative effort from multidisciplinary researchers navigating the complexities of forecasting and envisioning Asia’s work futures. This book offers valuable insights into the dynamic discourse on future studies, while offering a nuanced understanding of the work possibilities that lie ahead of Asia as well as deciphering Asia’s evolving impact and roles within the broader global context. This is an insightful read for scholars with an interest in Asian work and future studies.